PENGARUH PEMBERIAN MEDIA VIDEO INTUBASI TERHADAP KETERAMPILAN PEMASANGAN ENDOTRACHEAL TUBE PADA MAHASISWA KEPERAWATAN ANESTESIOLOGI UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Sari, Putri Mayang; Dewi, Ratih Kusuma; Rohmah, Astika Nur (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose: This study is aimed to determine the impact of intubation video media on the endotracheal tube insertion competence of Anesthesiology Nursing students at Universitas 'Aisyiyah Yogyakarta. Methods: This research employed a quantitative methodology utilizing a pre-experimental design including a one-group pretest and posttest approach, without a control group. The sampling method employed was simple random sampling utilizing an observation sheet as the instrument. The study's respondents were 40 individuals from the overall population of 157 Anesthesiology Nursing students from the 2021 batch. The employed statistical test was the Wilcoxon Signed Rank Test. Results: Statistical analysis revealed that before exposure to video media, 35 respondents (87.5%) were classified as less skilled, however after viewing of video media, 25 respondents (62.5%) were classified as skilled. The Wilcoxon test obtained a p-value of 0.000, indicating that the significance level was below 0.05 (sig. 0.000 < 0.05), therefore leading to the rejection of h0 and the acceptance ha. Conclusion: Video medium for intubation could help improve endotracheal tube insertion proficiency among Anesthesiology Nursing students at Universitas 'Aisyiyah Yogyakarta.